Long-read sequencing reveals absence of 5mC in Ogataea parapolymorpha DL-1 genome and introduces telomere-to-telomere assembly - Eremin, Andrey; Sergeev, Alexander; Kopylov, Arthur; Rodin, Vladimir; Malyshev, Daniil; Panova, Tatiana; Polyakov, Igor; Zvereva, Maria (Frontiers in Genetics, 2025)
BackgroundOgataea parapolymorpha DL-1 is a versatile thermotolerant organism with numerous applications in biotechnology, particularly in the production of recombinant proteins and the study of methanol metabolism and peroxisome functions. This study presents a comprehensive genome and methylome analysis of Ogataea parapolymorpha DL-1 using long-read sequencing technology. The research builds upon previous short-read sequencing efforts, revealing enhancements in genome assembly and epigenomic insights.MethodsWe used long-read sequencing technology to achieve a telomere-to-telomere (T2T) genome assembly of Ogataea parapolymorpha DL-1. High-quality reads were obtained and assembled de novo, followed by polishing to enhance accuracy. The genome was analyzed to identify coding genes, telomeric motifs, rRNA genes, and methylation patterns, including the detection of 5mC and 6 mA modifications. Epigenetic features were further assessed and validated through liquid chromatography-mass spectrometry.ResultsKey findings include the absence of 5 mC DNA modification and the presence of 6 mA in the genome, unusual telomere regulation mechanism based on the addition of non-telomeric dT and the introduction of long-read enhanced telomere-to-telomere assembly.ConclusionThis work provides deeper insights into the yeast’s genome organization and methylation patterns, contributing to the understanding of its genetics and therefore potential biotechnological applications.